Oral Formulaic Language in the Biblical Psalms - Culley, Robert, C. (Book collections on Project MUSE., 1967)
In Oral Formulaic Language in the Biblical Psalms, Robert C. Culley discusses dynamics involved in oral composition of poetry, particularly regarding Biblical poetry.